Big data analytics and key success factor in achieving competitive advantage and performance of small medium enterprises: literature review - Didi Tarmidi; Indra Taruna; Anton Budi S; Vina Marinda S (Institute of Computer Science (IOCS), 2023)
Along with the rapid changes in technology, many small and medium-sized enterprises (SMEs) have leveraged Big Data Analytics and other factors to drive digital transformation to gain a competitive advantage and improve performance. Making smart decisions based on data will help small and medium-sized companies get through the wave toward larger investment targets. The successful implementation of Big Data Analytics and other factors depends on alignment with aspects of an organization, technology, and human resources. Identifying critical success factors (CSFs) in driving Big Data innovation is critical to addressing the challenges surrounding Big Data Analytics and its application. This study aims to examine a systematic literature review that explains the concept of Big Data Analytics and the key success factors in achieving competitive advantage and performance of small and medium-sized companies. By conducting a systematic literature review analysis for studies related to key success factors and Big Data Analytics during the research period on data needs, there were 50 sources of articles analyzed to identify the concept based on its classification. Referring to the descriptive qualitative analysis method for the selected literature section, the findings of this study succeeded in identifying 48 critical success factors from the implementation section of Big Data Analytics by proposing schemes and frameworks in 4 categories, namely: Organization, Technology, Human Resources (People) and Management Data Governance. These findings can be used as a reference for successful strategies and implementation of Big Data Analytics by formulating them into a more effective database form to improve the performance of small and medium-sized companies in achieving competitive advantage.